PENGOLAHAN LIMBAH FLY ASH DAN BOTTOM ASH (FABA) MENJADI PRODUK KOMERSIL DI DESA SEKURO - Yayan Adi Saputro; Eka Nailis; Muhammad Faizal Ramadhan; Jati Widagdo; Samsul Arifin (Institut Teknologi dan Bisnis Swadharma, 2023)
Sekuro is one of the villages in the Mlonggo sub-district, Jepara Regency. Geographically, Sekuro village has a lot of potential because of its strategic location. Apart from that, Sekuro Village also has potential human resources that have not yet been absorbed. To achieve the goal of Community Service, namely the creation of creative products to realize an increase in the community's economy and to solve problems currently being faced by the Sekuro village community in particular. So the approach method used is direct practice and mentoring methods along with teaching aids direct practice methods. The implementation of community service activities is focused on the Sekuro village community who have an interest in fly ash and bottom ash waste management and those who have pilot building material businesses. Some of the programs that have been implemented, namely the offer of cooperation in paving blocks for village development, training in making products from this waste. All participants looked enthusiastic in participating in the whole series of service activities carried out. So that from these activities there is input for assistance to be carried out to market the products produced in the form of paving, bricks, and ornaments.